Sagot :
Answer:
3009976jabvajwwgabs
Step-by-step explanation:
1+6#jahc
[tex]\large{\mathcal{SOLUTION:}}[/tex]
In the equation (x-h)² = 4a(y-k)
- the equation for the directix is y = k-a
[tex] \\ [/tex]
Given that:
- (x+4)² = -12(y+6)
- (x-(-4))² = -12(y-(-6))
where h = -4 and k = -6
[tex] \\ [/tex]
We know that 4a = -12 , so
- 4a = -12
- a = -12/4
- a = -3
Then , on the equation of directix y = k-a
- y = k - a
- y = -6 - (-3)
- y = -6 + 3
- y = -3
Therefore , the directrix is y = - 3
[tex] \\ [/tex]
[tex]\large{\mathcal{ANSWER:}}[/tex]
- the directrix is y = -3
[tex] \\ [/tex]